2011
DOI: 10.1124/jpet.111.179820
|View full text |Cite
|
Sign up to set email alerts
|

RETRACTION: Indole-3-Carbinol Enhances the Resolution of Rat Liver Fibrosis and Stimulates Hepatic Stellate Cell Apoptosis by Blocking the Inhibitor of κB Kinase α/Inhibitor of κB-α/Nuclear Factor-κB Pathway

Abstract: Hepatic stellate cells (HSC) play a pivotal role in liver fibrosis, and the clearance of activated HSC by apoptosis is associated with the resolution of liver fibrosis. The development of strategies that promote this process in a selective way is therefore important. We evaluated the effects of indole-3-carbinol (I3C), a nutritional component derived from vegetables from the Brassica family, on liver fibrosis and HSC apoptosis. The in vivo therapeutic effects of I3C were monitored in three rat models of liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…However, pre-treatment with indole-3-carbinol exerted a marked anti-inflammatory activity, where the levels of pro-inflammatory markers were significantly reduced when compared to the cisplatin group. Several studies had shown that indole-3-carbinol has a marked anti-inflammatory properties in vitro 18 19 as well as in vivo 18 20 21 . Accumulation of platinum was found to play a role in cisplatin-induced nephrotoxicity 46 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pre-treatment with indole-3-carbinol exerted a marked anti-inflammatory activity, where the levels of pro-inflammatory markers were significantly reduced when compared to the cisplatin group. Several studies had shown that indole-3-carbinol has a marked anti-inflammatory properties in vitro 18 19 as well as in vivo 18 20 21 . Accumulation of platinum was found to play a role in cisplatin-induced nephrotoxicity 46 47 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that indole-3-carbinol has the ability to increase the activity of some anti-oxidant enzymes such as hemoxygenase-1 and glutathione transferase 16 . Besides, several studies had confirmed the anti-inflammatory activities of indole-3-carbinol in a variety of animal models such as aspirin-induced gastric ulcer 17 , liver fibrosis 18 , lipopolysaccharide-induced acute lung injury 19 and high fat diet-induced obesity 20 . In fact, indole-3-carbinol had been found to reduce the expression of pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α and NF-kB 18 19 21 .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The anticancer activity of I3C is also reflected in a number of signal transduction pathways associated with the inhibition of cell growth. Previous studies have evaluated the inhibition effects of I3C on the prosurvival PI3K/Akt[3], [8], [9] and nuclear factor-κB[10] signal transduction pathways. I3C also down-regulates mitogen-activated protein kinases (MAPK) expression[11].…”
Section: Introductionmentioning
confidence: 99%
“…In some signal transduction pathways that were associated with the cell growth inhibition, the anticancer activity of I3C is also reflected. the inhibition effects of I3C have been evaluated by previous studies on the PI3K/Akt pathway [2,7,8] and nuclear factor-kB [9] signal transduction pathways. And mitogen-activated protein kinases (MAPK) expression was also been down-regulated by I3C [10].…”
Section: Introductionmentioning
confidence: 99%